Depletion of miR-380 mitigates human bronchial epithelial cells injury to improve chronic obstructive pulmonary disease through targeting CHRNA4. (February 2020) - Wu, Xiujun
Abstract: Background: Chronic obstructive pulmonary disease (COPD) not only causes respiratory damage, but also affects circulatory function, which can be life-threatening in severe cases. Therefore, it is very essential to reveal the molecular mechanism of its pathogenesis. Methods: Human Bronchial Epithelial cells were exposed to 20% cigarette smoke extract (CSE) condition to simulate the cells in COPD patients. GEO database was applied to analyze the expression of miR-380 in COPD patients. The expression level of miR-380 in CSE model was determined with qRT-PCR. Cells proliferation, apoptosis, and inflammation response-related factors were detected with cell counting kit 8, flow cytometry, and Western blot, respectively. A correlation between miR-380 and Cholinergic Receptor Nicotinic Alpha 4 subunit (CHRNA4) was predicted with bioinformatics software, and confirmed by dual luciferase assay. Rescue assay was applied to explore further relationship between miR-380 and CHRNA4. Results: miR-380 showed a tendency of high expression in COPD patients and CSE models. Overexpression of miR-380 promoted the inhibitory effect of cells proliferation, and promotion effects of cells apoptosis and inflammation response, which were caused by CSE. CHRNA4, which was lower expressed in COPD patients, was affirmed as a target of miR-380 and negatively modulated by miR-380. Rescue assay indicated that exhausting of CHRNA4 attenuated the moderating effects of miR-380 inhibitor on cells damage induced by CSE. Conclusions: Depletion of miR-380 alleviated cells damage caused by CSE through targeting CHRNA4, suggesting that miR-380/CHRNA4 may serve as novel therapeutic targets for COPD treatment. Highlights: miR-380 was overexpressed in COPD patients and CES-induced cells. Depletion of miR-380 attenuated cell damage caused by CSE. CHRNA4, as a direct target of miR-380, was down-regulated in COPD patients. Knockdown of CHRNA4 promoted the protective effect of miR-380 inhibition on cell injury caused by CSE.